Learn to draw exciting anime & manga characters lessons from 100 professional Japanese illustrators (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2023)
"Imagine an art class taught by 100 professional Japanese manga and anime illustrators. In much the same way, this essential guide gathers the collective knowledge, tips and techniques from over 100 anime and manga artists. The lessons cover everything from the basics of figure drawing and posing to advanced cutting-edge digital illustration and colouration techniques"--Publisher's description.